A demographic and career profile of municipal CAOs in Canada: Implications for local governance. (March 2014) - O'Flynn, Patrick Eamon; Mau, Tim A.
<x xml:space="preserve">Abstract</x> Abstract Little has been written about the Canadian municipal chief administrative officer (CAO). Given the growing importance of municipalities, it is an important gap in the literature. This article depicts CAOs as a group of older white men, highly educated and very experienced. Given the impending retirement of a significant number of CAOs, municipalities have an opportunity to achieve a greater degree of representativeness. The authors identify a number of research trajectories to enhance our knowledge and understanding of this critical administrative position. Sommaire Il existe peu de documents sur les chefs des services municipaux au Canada. Étant donné l'importance croissante des municipalités, cela représente une grave lacune dans la documentation. Cet article décrit les chefs des services municipaux comme un groupe d'hommes blancs d'un certain âge, ayant un haut niveau d'études et une grande expérience. Comme un grand nombre d'entre eux vont prendre leur retraite d'ici peu, les municipalités ont une occasion de parvenir à un plus grand degré de représentativité. Les auteurs identifient un certain nombre de pistes de recherche pour améliorer nos connaissances et notre compréhension de cette fonction administrative cruciale.